Os reflexos da variação das vogais postônicas finais /o/ e /e/ no processo de aquisição da escrita dos jovens e adultos - Nascimento, Tatiana Dantas do (2017)
The main goal of this study was to provide to the researcher the opportunity to reflect his practice through didactic-pedagogical workshops applied to 15 students of Cycle I of Adult Education of a public school in João Pessoa. Focused on the textual genre List, it contains didactic strategies to work on the variation of the final postonic vowels /e/ and /o/ present in the speech and its reflection in writing, especially those that are in the process of language acquisition. This variation was selected for the accomplishment of this study, after the observation that its transposition to writing is quite common. The didactic workshops were elaborated respecting the oral variant of the student, but with the purpose of expanding his knowledge to the appropriate form of writing. Thus, to work on the phenomenon of the variant in question, it became necessary to know sociolinguistics and linguistic variations, especially the phonological-phonetic ones. In this sense, we try to lead the students to the understanding that the average vowels /e/ and /o/ are usually pronounced [i] and [u] in unstressed, pretonic, postonic syllables (BORTONI-RICARDO, 2004, p.80), and, specifically, to discuss the variation of the final postonics, as in bolo bol[u] and doce doc[i], quite productive in brazilian portuguese. Not being stigmatized, this process ends up being spoken by people of different social classes and levels of literacy, but the same does not happen in writing, since it is a modality of the language that requires adaptation to the orthographic pattern. The results of the research showed that the students who received the intervention performed the monitoring in a more conscious way, while the students who did not receive the same type of intervention did the monitoring in a few words, performing significantly the transposition of the variation, present in speech, for writing. In this direction, the role of the teacher is extremely important to create situations and strategies of intervention that help students to understand that certain variants used in orality are not suitable for writing.